Implementasi Metode Ceramah Plus dalam Komsel selama Pandemi - Sarah Farneyanan; Roy Pieter; Josiharu Edmund Here; Immanuel Eko Widiantoro (STT Kingdom, 2022)
The pandemic challenges the church to remain productive and creative in order to answer and live out its duties and vocations for humans in this world. Through komsel as the pastoral arm of the church for its citizens, it is necessary to implement an appropriate approach strategy so that the faith of the church members remains strong and even grows. The lecture plus method is one of the methods applied in komsel during the pandemic so that church members move towards an understanding of the Word so that their faith can be strong and grow. The method used in this research is descriptive qualitative. The results of the study show that there are two kinds of implementations of the lecture plus method which are applied in komsel during the pandemic, the first is the voice of the pastor and the second is the outline of the sermon.